2014
DOI: 10.1590/s1415-47572014000100011
|View full text |Cite
|
Sign up to set email alerts
|

The lowest diploid number in Testudines: Banding patterns, telomeric and 45S rDNA FISH in Peltocephalus dumerilianus, 2n = 26 and FN = 52 (Pleurodira, Podocnemididae)

Abstract: The karyotype of the big-headed Amazon River turtle, Peltocephalus dumerilianus, is characterized based on a sample of seven juveniles from Reserva Biológica do Rio Trombetas, Pará State, Brazil (1°30′ S, 56°34′ W). Here we present the first results on GTG and CBG-banding patterns, Ag-NOR staining and FISH, with telomeric and 45S rDNA sequences as probes. A cytogenetic comparison with related Podocnemidae is also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 12 publications
1
13
0
1
Order By: Relevance
“…Our finding that the NOR is located on the first chromosome pair of both PEX and PUN, associated with a secondary constriction, is consistent with previous observations in P. expansa and P. sextuberculata [ 13 , 42 ]. This suggests that the NORs are highly conserved in family Podocnemidae.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding that the NOR is located on the first chromosome pair of both PEX and PUN, associated with a secondary constriction, is consistent with previous observations in P. expansa and P. sextuberculata [ 13 , 42 ]. This suggests that the NORs are highly conserved in family Podocnemidae.…”
Section: Discussionsupporting
confidence: 93%
“…6 ). In contrast, Ventura et al [ 42 ] reported that the secondary constriction region of Peltocephalus dumerilianus presented a large block of heterochromatin. The telomeric probes hybridized with atypical regions, such as centromeres, perhaps reflecting the random amplification of telomere-like sequences or telomere remnants that remained following centric fusions that occurred during evolution [ 10 , 14 , 43 ].…”
Section: Discussionmentioning
confidence: 95%
“…The diploid number in turtles ranges from 2n = 26 in Peltocephalus dumerilianus [Killebrew, 1975a;Ventura et al, 2014] to 2n = 68 in Carettochelys insculpta [Bickham et al, 1983] with an average of 2n = 52 given our current knowledge of turtle chromosomes [Olmo and Signorino, 2005] ( fig. 1 ).…”
Section: Evolution Of Turtle Karyotypesmentioning
confidence: 99%
“…The members of order Testudines may be subdivided in two suborders (Cryptodira and Pleurodira) and comprise one of the oldest lineages of existing vertebrates [ 1 ]. Studies have revealed a high degree of karyotypic variation in this order; the diploid numbers (2n) range from 26 in Peltocephalus dumerilianus (Pleurodira, Podocnemididae) [ 2 , 3 ] to 68 in Carettochelys insculpta (Cryptodira, Carettochelyidae) [ 4 , 5 ], with 2n = 52 reported as the most frequent diploid number [ 5 ]. The karyotypic diversity of the Testudines is attributed mainly to the presence/absence of microchromosomes.…”
Section: Introductionmentioning
confidence: 99%